Postfazione. La fragilità della sovranità tra colonialismi ed epistemologie dei sud del mondo - Flavia Cuturi (Archivio Antropologico Mediterraneo)
The contribution aims to highlight dynamics and processes that are common to the articles in the monographic dossier, dedicated to food sovereignty, security and sustainability in different island contexts. Focusing on the intersections between these processes and current and past forms of colonialism, the intent of the work is to outline the historical relational complexity between dependence and autonomy in the food supply chain, highlighting the common socio-environmental "wounds" rooted in a history of colonial domination and persistent discrimination. Through a diachronic and positioned gaze, the objective is to bring the notions of "terraformation" and "coloniality" into dialogue with the different epistemologies and ontologies of the global South represented by the insular contexts proposed in the dossier; in them, food sovereignty, marginalization and "isolation", the result of endocolonial practices that perpetuate socio-environmental inequalities and conflicts, are combined with forms of resistance, defense of territorial autonomy, and the demand for health and well-being. The contribution proposes, as a synthesis, an ethnographic immersion in the complex situation experienced by the ikoots of San Mateo del Mar (Oaxaca, Mexico) faced with difficult life choices, oppressed by the threat represented by massive unsustainable government development projects.